Functional recovery of stroke patients with postacute care: a retrospective study in a northern medical center. Issue 5 (May 2019) - Huang, Hui-Chi; Tsai, Jui-Yao; Liu, Tzu-Ching; Sheng, Wen-Yung; Lin, Tzu-Chun; Lin, Ching-Wei; Lee, I-Hui; Chung, Chih-Ping
Abstract : Background: Taiwan's NHI Administration proposed a nationwide postacute care-cerebral vascular disease (PAC-CVD) program, which transfers stroke patients at postacute phase in medical centers to community hospitals. Its aim is mainly to prevent a prolonged stay in medical centers, which usually results in higher medical costs. The present study evaluated the 3-months functional outcomes of stroke patients receiving PAC-CVD. Methods: We retrogradely retrieved patients' data from Stroke Registry of a Northern medical center. Patients admitted between January 2014 and March 2018 were screened. We included patients receiving PAC-CVD and age/sex/stroke severity/functional status-matched acute stroke patients (regular rehabilitation group). Baseline clinical characteristics and 3-months functional outcomes were analyzed. We defined 3-months mRS 0 to 2 as better, 3 to 4 as same, and 5 to 6 as worse functional recovery. Results: One-hundred-and-seventy-three patients receiving PAC-CVD and 173 matched controls (68.2 ± 14.0-years-old, 68.5% ± 11.22% men) were recruited. All patients were with mRS 3 to 4 at discharge from our medical center. The distributions of 3-months functional recovery in two groups were as follows: better/same/worse 3-months functional outcomes, PAC-CVD = 40.4%/57.8%/1.8%; controls (regular rehabilitation) = 33.9%/50.3%/5.8%. Multivariate analyses adjusted for age, sex, NIHSS, and cardiovascular risk factors were performed to evaluate whether PAC-CVD predicted better or poor functional outcomes. The results showed that compared with controls, PAC-CVD group had similar frequency of better functional recovery (odds ratio [OR] = 0.97, 95% CI = 0.54-1.74, p = 0.924) but less frequency of worse functional outcomes (OR = 0.08, 95% CI = 0.08-0.84, p = 0.035). Conclusion: About one-third of patients with mRS 3 to 4 recovered well in 3-months after stroke in both PAC-CVD and regular rehabilitation groups. Our results showed that PAC-CVD program can significantly decrease functional decline after acute stroke.